PENGARUH MOTIVASI DAN UPAYA PENCEGAHAN TERHADAP KINERJA KADER KESEHATAN - Rendi Salam (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Dengue cases always occur in every year. This requires the people involved to improve their performance, including the health cadres. This study aims to analyze the effect of motivation and prevention efforts on the performance of health cadres. Design research conducted in the preparation of this is associative quantitative. The research data were obtained from the statement of health cadres in Pamulang Health Center, which amounted to 50 people. The analysis technique uses regression with several other analyzes needed. Research facts show that motivation is the most dominant variable in influencing employee performance, then effort. This confirms, if the performance of health cadres is very dependent on morale